Cyprus and its Neighbours in the Early Bronze Age. A Study of Bronze Objects. Ph. D. - Watkins, Trevor Francis (1964)
F. J. Tritsch; Typescript; Typology of metal objects, many of them unpublished. No Cypriot objects found outside Cyprus, but there is evidence for export of copper from Cyprus. New metal analysis tracing the material in manufactured metal objects to its original source. Trade routes.